Towards the Keplerian sequence: Realistic equations of state in rapidly rotating neutron stars - Koliogiannis Koutmiridis, Polychronis; Moustakidis, Charalampos (HNPS Advances in Nuclear Physics, 2020)
Neutron stars are among the densest known objects in the universe and an ideal laboratory for the strange physics of super-condensed matter. In the present work, we investigate the Keplerian (mass-shedding) sequence of rotating neutron stars by employing realistic equations of state based on various theoretical nuclear models. In particular, we compute the moment of inertia and angular momentum of neutron stars against mass-shedding and secular axisymmetric instability. We mainly focus on the dependence of these properties from the bulk properties of neutron stars. Another property that studied in detail, is the dimensionless spin parameter (kerr parameter) of rotating neutron stars at the mass-shedding limit. In addition, supramassive time evolutionary rest mass sequences, which have their origin in general relativity, are explored. Supramassive sequences have masses exceeding the maximum mass of a non-rotating neutron star and evolve toward catastrophic collapse to a black hole. Important information can be gained from the astrophysical meaning of the kerr parameter and the supramassive sequences in neutron stars. Finally, the effects of the Keplerian sequence, in connection with the latter, may provide us constraints on the high density part of the equation of state of cold neutron star matter.